The evil of giving life. An essay in Spanish antinatalism : Review of: Miguel Ángel Castro Merino (2023): El Maldito regalo de nacer. Un ensayo antinatalista. Ed. Punto Didot, Madrid, 375 pp. - Mantella, Rubén Omar (Analysis. Journal of Philosophical Research, 2024)
Review of: Miguel Ángel Castro Merino (2023): El Maldito regalo de nacer. Un ensayo antinatalista. Ed. Punto Didot, Madrid, 375 pp.